Empowerment of Farmer Women’s Group (Case Study of Edelweis Farmer Women’s Group) in Payakumbuh City - Hidayatul Ulfa; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research is motivated by the empowerment of women farmer groups in the community. The aim is to improve skills and increase community knowledge through women farmer groups so that they can help with daily needs and increase people's income and improve the welfare of the people of Sawahpadang Aua Kuniang village. The purpose of this study is to see the process of empowering women's farmer groups in edelweiss women's farmer groups, and the impact of empowering women's farmer groups.This research is based on a qualitative approach with case study research. The sources of data in this study were the chairperson, secretary, treasurer, and members of the Edelweiss Women's Farmers Group. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validation technique uses triangulation.The results of the research show that (1) the process of empowering women farmer groups has 3 stages, starting from the awareness stage, the capacity stage, and the power-giving stage, (2) the impact of empowering women farmer groups is that the community has practiced in the yard of their homes to plant useful plants. for daily needs, can also be used by the community to increase income. It is recommended that all those involved in the edelweiss farmer women's group can further develop their skills so that they can enter the market area and can prosper family life.Keywords: Empowerment, Women Farmer Group